New species of Sargassum-boring Limnoria Leach, 1814 (Crustacea, Isopoda, Limnoriidae) from Japan - Yoshino, Hiroki; Kambara, Yuriko; Kajiwara, Shota; Ohsawa, Takeshi A. (Zootaxa, 2021)
A new marine Sargassum-boring species of Limnoria (Limnoriidae) is described on the basis of specimens obtained at Kamogawa-shi, Chiba Prefecture, Japan. Limnoria aspera sp. nov. shares a reduced mandibular palp to a seta, algal-feeding, and the clavate shaped epipod of the maxilliped with the other species of non-mandibular-palp group. L. aspera sp. nov. differs morphologically from the congeneric species by secondary unguis of pereopods and unique carinae of pleonite 5 and pleotelson. We describe the sequences of the mitochondrial COI gene and the nuclear 28S rDNA gene. L. aspera sp. nov. differs by 14.2–18.0% in p-distance based on COI sequences from other Japanese species, L. furca and L. nagatai.